(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the issues of penetration into the Ferghana Valley of ancient agricultural tribes such as the Sarazm culture and a whole layer of culture, indicating the presence in this region of finds that can be dated from the era of the Late Eneolithic and Early Bronze Age, which later became the basis of the Chust culture.